Usage of experience of development of territories with similar socio-economic characteristics taken as a whole as an instrument of Kronshtadt sustainable development - Maria Kozyreva (European Regional Science Association (ERSA), 2003)
This article gives an account of approach to design of sustainable regional development concept and presents the results of its usage on the Kronshtadt example. In the today's world most of the regions are faced with a crucially important task, which is to take the way of sustainable development. There is a number of instruments, which could be successfully used in sustainable regional development concept design. One of then is a usage of experience of development of territories with similar socio-economic characteristics taken as a single whole. First of all, usage of this instrument allows to reveal economic industries that have been effectively developing in regions with similar characteristics and in the close economic conditions. Secondly, it allows to analyze measures that were taken to develop those industries and appraise their efficiency. This instrument gives an opportunity to ?learn by other people's mistakes'. At the same time it requires to take into account internal conditions and the law-governed nature of the investigated region. Usage of this instrument could be demonstrated on Kronshtadt example. Kronshtadt is a town situated on the Kotlin Island in the Gulf of Finland, and presents an administrative district and municipal district of Saint-Petersburg. As the main socio-economic characteristics of the region were selected the following: -island territory; -favorable geographic position on the intersection of the sea and tourist routes; -naval dockyard and naval base town which lost its historic role and majority of government investments as the Cold War came to an end. The following regions were classified as territories similar to Kronshtadt according to socio-economic characteristics taken as a single whole: Kaliningrad region, Russia; Gibraltar island, Great Britain (one of the most important naval bases of Great Britain and key strong point of NATO at the Cold War time); Malta island (former English colony) and such historic naval dockyard and maritime towns as Medway/Chatham, Great Britain; Portsmouth, Great Britain; Rochefort, France; San-Fernando, Spain; Suomenlinna, Finland; Karlskrona, Sweden. The experience of development of these territories was systematized in the following directions: -most effectively developing economic industries; -projects that were financed by regional or federal government investments; -measures that were taken to attract commercial investments; -rules that were accepted to transfer the property rights on naval dockyards; -socio-economic effect from the implementation of the development programs. This article presents the results of the conducted research and provides recommendations for Kronshtadt sustainable development.
Keywords: 330